Fasciola hepatica case with hemobilia. - Bahcecioglu, Ibrahim Halil; Ataseven, Hüseyin; Aygen, Erhan; Coskun, Serdar; Kuzu, Nalan; Ilhan, Fulya (My University, 2007)
Fasciola hepatica (FH) can lead to important hepatobiliary diseases. Here we present a case of hemobilia associated with biliary FH, which is quite a rare case. The 41-year-old patient, who underwent common bile duct exploration due to hemobilia, was found to have arterial bleeding associated with ulcer caused by a dead parasite in the common bile duct. Hemobilia is a very rare complication associated with FH. When searching for the cause of hemobilia, FH should be considered.
Keywords: Adult; Animals; Common Bile Duct Diseases; Fasciola hepatica; Fascioliasis; Hemobilia; Humans; Male; adult; animal; article; case report; common bile duct disease; Fasciola hepatica; fascioliasis; hemobilia; human; male